GROWTH AND PRODUCTION OF POHPOHAN Pilea melastomoides (Poir.) Wedd. DAN REUNDEU (Staurogyne elongate Kuntze) AND ON VARIOUS SHADING LEVELS - Sutandi, Intan Apriani; Rahayu, Arifah; Rochman, Nur (Universitas Djuanda Bogor, 2017)
This study was aimed at assessing the effects of shade on the growth, productivity of indigenous vegetables pohpohan and reundeu. A split-plot design was used. The main plot was shade treatments consisting of four levels, namely 0% (no shade), 25%, 50%, and 75%. The subordinate plot was the seed origins, namely Sukabumi, Cianjur, and Bogor. The arrangement of the main and sub plots was done based on a completely randomized design. Results showed that in pohpohan increased plant height was found in 50% shade treatment, while leaf length and width was found to be increased in shade treatment up to 75%. Leaf length and width of pohpohan plants of Bogor origin were higher than those of pohpohan plants of Cianjur and Sukabumi origins. In reundeu plants, no effects of shade treatments were found in all variables measured. Reundeu plants of Bogor and Cianjur origin were found to be superior in plant height, leaves number, length, and width, and fresh and dry weight. Pohpohan plants were potential to be grown under shades. Key words: seed origin, plant height, pohpohan, reundeu, Bogor